Give a girl a job : reflections on ethnography, money and suffering among South African women - Cruz, Daniel Mendonça Lage da (2024)
Tese (doutorado) — Universidade de Brasília, Instituto de Ciências Humanas, Departamento de Antropologia, Programa de Pós-graduação em Antropologia Social, 2024.